Pain in the immediate puerperium: nursing care contribution - Juliana Vieira Figueiredo; Ana Virgínia de Melo Fialho; Glícia Mesquita Martiniano Mendonça; Dafne Paiva Rodrigues; Lúcia de Fátima da Silva
ABSTRACT Objective: to analyze the contribution of clinical nursing care to the mother who has recently given birth with immediate postpartum pain based on the Kolcaba's Theory of Comfort. Method: qualitative study by the research-care method. Three nurses, who provided care for women in the immediate puerperium as caregiver-researchers and 30 postpartum women, were admitted to a public maternity hospital. A semi-structured interview was used for data collection, from which the thematic analysis of the content was carried out. Results: nursing care with influences from the biomedical model was observed, but it expresses concern when being cared for. It offers administration of medications, guidelines and non-pharmacological measures for pain relief. Final considerations: nursing care based on the Theory of Comfort contributed to pain relief in the immediate puerperium.